Adjuvant urokinase: percutaneous drainage of post lower segment cesarean section intra-abdominal abscess - Khade, Shweta Avinash; Jadhav, Balaji; Meena, Preeti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
The mortality in abdominal abscess is high, however the outcome has improved due to advances in image guided percutaneous interventional techniques. The main indications for the catheter drainage include treatment or palliation of sepsis associated with an infected fluid collection, and alleviation of the symptoms that may be caused by fluid collections by virtue of their size, and site. The single abscesses may be drained with ultrasound guidance only, whereas the multiple abscesses usually require computed tomography (CT) guidance and placement of multiple catheters. Percutaneous drainage provides an effective and safe alternative to more invasive surgical drainage but the success rate is lower for abscesses that have septa and are multilocular. Several clinical and in vitro studies suggest urokinase may be useful in such cases. To the knowledge, however, there has been no case of post LSCS intra-abdominal abscess in which intracavitary urokinase was administered. Therefore, we report a case of post LSCS multiseptated intra-abdominal abscess occurring in a 21-year-female. Conventional percutaneous tube drainage failed, but the use of transcatheter intracavitary urokinase was successful. Our results showed no significant change in hematologic studies and no bleeding complications. Intracavitary urokinase can be given safely during percutaneous drainage of an abscess, with no associated bleeding complications or changes in coagulation parameters.